Performance Analysis and Optimization of SOFC/GT Hybrid Systems: A Review - Qiao Yuan; Xiongzhuang Li; Shuo Han; Sijia Wang; Mengting Wang; Rentian Chen; Sergei Kudashev; Tao Wei; Daifen Chen (Energies, 2024)
This review provides an overview of the solid oxide fuel cell/gas turbine (SOFC/GT) hybrid system, highlighting its potential as a highly efficient and low-emission power generation technology. The operating principles and components of the SOFC/GT system, as well as the various configurations and integration strategies, are discussed. This review also examines the performance, advantages, and challenges of the SOFC/GT system, and discusses the research and development efforts aimed at improving its efficiency, reliability, and cost-effectiveness. This work provides an overview of the research conducted in the area of SOFC-based hybrid systems, which is expected to be beneficial for researchers who are interested in this area.